Fig. 3 in Two New Species of Free-living Marine Nematodes (Nematoda: Axonolaimidae and Tripyloididae) from the Coast of Antarctica - Shimada, Daisuke; Suzuki, Atsushi C.; Tsujimoto, Megumu; Imura, Satoshi; Kakui, Keiichi (Zenodo, 2021)
Fig. 3. Odontophora odontophoroides sp. nov. A, female body (ICHUM 5490); B, female head with open mouth (ICHUM 5490); C, female posterior region (ICHUM 5490); D, vaginal region (ICHUM 5490). Scale bars: A, 500 µm; B, 20 µm; C, D, 100 µm. : Published as part of Shimada, Daisuke, Suzuki, Atsushi C., Tsujimoto, Megumu, Imura, Satoshi & Kakui, Keiichi, 2021, Two New Species of Free-living Marine Nematodes (Nematoda: Axonolaimidae and Tripyloididae) from the Coast of Antarctica, pp. 49-63 in Species Diversity 26 (1) on page 54, DOI: 10.12782/specdiv.26.49, http://zenodo.org/record/5736867